Proliferative Glomerulonephritis with Monoclonal Immunoglobulin Deposition: Report of Two Cases and Review of Literature - Renu Mariam Thomas (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Here we report two cases of proliferative glomerulonephritis with monoclonal IgG deposits, a form of renal involvement by monoclonal gammopathy that mimics immune complex glomerulonephritis. Case 1 presented with incidental proteinuria and a renal biopsy showed mesangioproliferative glomerulonephritis with monoclonal IgG kappa deposits on immunofluorescence examination. He remains stable after one year follow up. Case 2 presented with rapidly progressive renal failure and renal biopsy showed rescentic membranoproliferative glomerulonephritis with monoclonal IgG kappa deposits on immunofluorescence study.  He  showed  no  response  to  aggressive  immunosuppressive  medication  and  plasmapheresis  and remained  anuric.  He  underwent  renal  transplantation  three  months  later  but  disease  recurred  in  the allograft,  which  was  diagnosed  on  a  biopsy  one  and  a  half  months  post-transplant.  Extensive  work  up for  underlying  paraprotein  disease  was  negative  in  both  patients.  Our  aim  is  to  expand  awareness  and highlight the heterogeneity in the clinical presentation, histology and outcome of this rare entity.